Sleep Disturbances During the Menopausal Transition: The Role of Sleep Reactivity and Arousal Predisposition. Issue 4 (4th July 2022) - Ballot, O.; Ivers, H.; Ji, X.; Morin, C. M.
ABSTRACT: Background: Sleep disturbances are common during the menopausal transition and several factors can contribute to this increased incidence. This study examined the association between sleep reactivity, arousal predisposition, sleep disturbances, and menopause. Methods: Data for this study were derived from a longitudinal, population-based study on the natural history of insomnia. A total of 873 women (40–60 years) were divided into two groups according to their menopausal status at baseline: reproductive (n = 408) and postmenopausal (n = 465). Participants were evaluated annually throughout the five-year follow-up period. Four questionnaires were used to examine sleep quality, insomnia severity, sleep reactivity, and arousal predisposition. The data were analyzed using two approaches: cross-sectional with a multivariate analysis and binary regression, and longitudinal with a linear mixed models using menopausal groups (3) x time (5) design. Results: Cross-sectional analyses showed that postmenopausal women reported significantly more severe insomnia and poorer sleep quality than reproductive women. Sleep reactivity and arousal predisposition were significant predictors of sleep disturbances. Longitudinal analyses revealed increased sleep disturbances in the two years before and after the menopausal transition. Sleep reactivity and arousal predisposition did not moderate the temporal relationship between menopausal transition and sleep disturbances. Conclusion: More sleep disturbances were reported during the menopausal transition, but those difficulties were not explained by sleep reactivity and arousal predisposition. These results suggest the involvement of other psychophysiological factors in the development of sleep disturbances during the menopause.